Cognitive Counseling in Handling Victims of Bullying of Children with Special Needs - A Malek, Mohd Ahsani bin (JURNAL KONSELING GUSJIGANG, 2024)
Bullying of children with special needs is a serious problem that negatively affects the psychological, social and academic conditions of children. This study aims to analyze the effectiveness of cognitive counseling in helping victims of bullying among children with special needs through a Systematic Literature Review (SLR) approach. A total of 17 scientific articles from 2014-2024 were reviewed thematically to identify the role of cognitive counseling in victim recovery. The results of the analysis show that cognitive counseling is effective in changing irrational thoughts, increasing self-confidence and developing emotion regulation skills in children with disabilities who are victims of bullying. The intervention also proved to be adaptive to individual characteristics and more optimal when supported by an inclusive and collaborative school environment. These findings confirm the importance of implementing cognitive counseling in guidance and counseling services in inclusive schools as an appropriate psychological assistance strategy for children with disabilities who are victims of bullying.